Intranet Network Optimization Using VLAN at Vocational High School Gedangan - Sa’diyah, Chalimatus; Islamiyah, Mufidatul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to optimize the intranet network at Vocational High School Gedangan by using Virtual Local Area Network (VLAN). The main goal is to enhance network performance and security, especially in environments with numerous users, where LAN structures face management and security challenges. Method: The research employs a qualitative descriptive method, utilizing observations and interviews with the school's IT staff to understand how VLAN is implemented and its advantages. The data collected is used to analyze how VLAN can improve network efficiency and flexibility. Practical Applications: By segmenting the network with VLAN, the school can better manage user access and isolate different departments or student groups. This helps prevent network congestion and reduces potential security threats, contributing to a more reliable and secure system for daily operations and learning processes. Conclusion: VLAN implementation at Vocational High School Gedangan significantly optimizes the network's performance and security, creating a more efficient and safer environment for both administration and educational activities.